Reconstruction of MaxEnt images from pet camera - (:unkn) unknown (RAD Association, 2017)
We study here one of the imaging techniques, used in nuclear medicine, called a Positron Emission Tomographic (PET) imaging that provides information about many biological processes that are essential to the functioning of the organ that is being visualized. Our emphasis is given to applications of the maximum entropy image reconstruction method called “Cambridge MaxEnt Package” (CMEP) for recovering images of the human brain from data obtained by PET camera. Computer simulations demonstrate its usefulness. © RAD Conference Proceedings. All rights reserved.
Keywords: Back projection; Ill-posed problems; Image reconstruction; Inverse problems; Maximum entropy; Nuclear medical imaging; Regression; Regularization